THE DEGREE OF FEDERAL INFLUENCE ON THE DEVELOPMENT VECTOR OF THE CHECHEN REPUBLIC - RESHIEV, Sulaiman (CENTRAL ASIA AND THE CAUCASUS, 2007)
The Chechen Republic is going through a difficult historical period in its development. A retrospective analysis of the nature of this process shows a clear correlation between the policy of the Federal Center and the vector of Chechnia’s sociopolitical development. The current state of affairs in the Chechen Republic results in large part from its tragic past. In studying the republic’s development, it is necessary, in my opinion, to examine three periods in their interconnection, because such an approach helps to gain a better understanding of the philosophy of its evolution. The Soviet period in the development of Chechnia was marked by great excesses in the national policy of the Union Center toward the republic. The starting point here was the absolutely monstrous deportation of entire peoples from their historical homeland in 1944. When the Chechens were allowed to return in 1957, their integration into peaceful constructive life in the Chechen-Ingush Autonomous Soviet Socialist Republic was a slow and painful process. This had a particularly adverse effect on the work of government bodies and economic management agencies. Until 1989 (that is, almost until the end of the Soviet period), not a single representative of the titular nationality had ever been elected as head of the regional Communist Party committee. Ethnic Chechens met with artificial barriers limiting their opportunities to work in a number of key ministries, departments and associations; they were never appointed to senior posts. A similar situation existed in higher and secondary education institutions in the republic. In the Soviet period, the economy of the Chechen-Ingush Republic was mostly based on the petrochemical complex. In the 1980s, industrial production had the leading place, accounting for 57% of the republic’s total output; agriculture contributed 17.8%, construction, 15.5%, and infrastructure sectors, 9.3%. The main role in industry was played by the fuel and energy complex, whose share in 1988 was 45.7% of commercial output and 67% of fixed assets. The Soviet period in the republic was marked by the development of large and highly productive deposits, and also by their intensive exploitation designed to maximize current revenue. This resulted in rapid depletion of reserves and mounting environmental problems, which led to a shortening of active development periods and to a premature decline and “winding down” of mineral production in many areas. This process gathered momentum in the republic in the 1960s-1980s. The average period of active development of oil-producing regions in Russia is around six years. Foreign experience shows that active field development in the oil and gas sector in many countries and regions is lengthened by means of moderate rates of extraction (primarily at major fields) and capacity reservation. For onshore oil fields, the rate of development is usually close to 2% of original recoverable reserves. That is why the active development period for many foreign oil-producing regions is dozens of years. A moderate extraction rate makes it possible not only to lengthen this period, but also to minimize costs and, consequently, to increase the profitability of oil and gas production.